2012
DOI: 10.2134/agronj2012.0185
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Cover Crop Benefits with Diverse Mixtures and an Alternative Termination Method

Abstract: Previous studies have demonstrated benefi ts of individual cover crop species, but the value of diverse cover crop mixtures has received less attention. Th e objectives of this research were to determine the eff ects of spring-sown cover crop mixture diversity and mechanical cover crop termination method on cover crop and/or cash crop productivity, soil moisture and N, and profi tability in an organic cropping system. An experiment was conducted between 2009 and 2011 near Mead, NE, where mixtures of two (2CC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 57 publications
(77 reference statements)
7
105
2
2
Order By: Relevance
“…Finally, uncertainty also relates to the difficulty, even impossibility, in accessing complete and accurate information about land-use practices at the landscape level, especially in time for management decisions (Williams 2011). This is particularly true when "pest managers" seek to adapt landscape heterogeneity to disrupt pest cycles and increase abundance of beneficial arthropods (Wortman et al 2012), which moreover may lead to conflicting recommendations.…”
Section: Uncertainty and Site-based Transitionmentioning
confidence: 99%
“…Finally, uncertainty also relates to the difficulty, even impossibility, in accessing complete and accurate information about land-use practices at the landscape level, especially in time for management decisions (Williams 2011). This is particularly true when "pest managers" seek to adapt landscape heterogeneity to disrupt pest cycles and increase abundance of beneficial arthropods (Wortman et al 2012), which moreover may lead to conflicting recommendations.…”
Section: Uncertainty and Site-based Transitionmentioning
confidence: 99%
“…However, under a dry continental climate as in Moldova, experience with cover crops is limited. It was hypothesized that in regions with low precipitation (< 500 mm yr −1 ), cover crops could have an adverse effect on agricultural productivity as the water available for subsequent main crops may be reduced (Blanco-Canqui et al, 2011;Stavi and Lal, 2013;Wortman et al, 2012;Unger and Vigil, 1998;Cherr et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Termination method and residue management can influence N mineralization, soil nutrient loss and availability, crop N uptake, weed communities and soil moisture availability (Mirsky et al, 2009;Parr et al, 2011;Wortman et al, 2012b). Yield is typically expected to improve with legume CCs, and when loss occurs, it is attributed to incomplete cover crop termination, increased moisture utilization by CCs leading to moisture deficit, or nutrient immobilization (Mischler et al, 2010a).…”
Section: Terminationmentioning
confidence: 99%
“…Liebl et al (1992) found that transpiration reduced available soil moisture during dry periods, but following no-till termination, CC residue conserved soil moisture relative to a no-till system without CCs. Given that the driest portion of the growing season in the western Corn Belt typically occurs after CC growth (i.e., June-August), potential soil moisture savings offered by the residue (post-termination) throughout the growing season may negate moisture deficits observed during CC growth (Wortman et al, 2012b).…”
Section: Terminationmentioning
confidence: 99%